EFFECTIVENESS OF THINK-PAIR-SHARE STRATEGY IN ENHANCING STUDENTS’ ACADEMIC ACHIEVEMENT AND INTEREST IN DIFFICULT CHEMISTRY CONCEPTS - Winifred Ifeoma Esiefa; Helen Drummond (Universitas Negeri Surabaya, 2026)
The failure rate in the subject chemistry at secondary school is on the increase and this has been attributed to students not understanding most of the difficult concepts which formed the foundation of the subject. The method that teachers adopt in the teaching of the subject and the manner the subject is taught may be factors that are responsible for poor performance. The methodology used is the quasi-experimental design using the pretest post-test non-equivalent control group. Quantitative and qualitative methods were employed. The population of the secondary schools used for the study was 1231, the sample size of 173 was used which was drawn using non-random sampling technique. Chemistry Achievement Test (CAT)Chemistry Interest Inventory (CII) and semi-structured interview were used for data collection. The instruments were test piloted and the internal coefficient obtained was 0.85 while the reliability index was 0.79. Mean and standard deviation were used to provide answers to the research questions and Analysis of Covariance (ANCOVA) was used to test the hypotheses. The students in the experimental group had higher interest levels with M=3.10 and Sd=0/43 for post-test compared to the students who were taught with conventional methods, with interest levels of M=2.77 and Sd=0.64. they also had higher achievement scores for the post-test in difficult chemistry concepts M=75.57 with Sd=13.76 than the control group M=63.40, SD=14.91. The think-pair-share strategy demonstrated an effective instructional approach for increasing student interest in the selected challenging chemistry topics: of solubility, hydrocarbon and metals and their compounds that were taught. The findings therefore underscore how effective this pedagogical strategy is in improving both students’ interest and achievement in these difficult chemistry concepts.